The significance of knowledge of social contexts to concept development in graphic design practice in New Zealand - Mauger, Stanley Philip (Curtin University, 2010)
This thesis investigates the question; what is the significance that a cross-section of New Zealand graphic designers placed on using knowledge of social contexts to inform their practice? It reveals whether graphic designers in the research, drew on knowledge of social contexts that arose from implicit knowledge, whether they relied on dedicated research to locate knowledge of social contexts and the extent to which that knowledge of social contexts was significant to their practice.The theoretical framework for the research was primarily based on Pierre Bourdieu’s concepts of habitus, social structure and practice, to find the degree to which knowledge of social contexts came out of either a conscious process of enhancing cultural capital in designers’ day-to-day practice, or from dispositions inculcated over designers’ lifetimes through habitus at various levels. Bourdieu’s sociological perspectives are particularly applicable to this research, because of the way in which he places great emphasis on cultural knowledge as the basis of cultural investigation.The ethnographic research modelled on Bourdieu’s methods, in which empirical studies are essential to theoretical research, used conversation analysis in which the reflexivity of the interviewer contributed strongly to the collection of data. The research method was based on a series of seven case studies conducted with New Zealand graphic designers of varying backgrounds and working situations, between 2002 and 2003. The research investigated how they had acquired knowledge of social contexts for practice and the importance that they placed on bringing this knowledge into their practice. The research group ranged from recent graduates to senior and accomplished graphic designers.Graphic designers showed the significance of knowing about social contexts, through the cultural capital that was important to their practice and to their positions in the graphic design field. This research has highlighted the difficulty that designers encountered, to varying degrees, in identifying how knowledge of social contexts came into their practice or even how they had acquired this knowledge.Knowledge of social contexts was shown to be derived from designers’ own social structures and the durable dispositions and practice relative to their background, from the habitus of the internal culture of a designer's firm, from within the wider field of graphic design practice and the changing dispositions arising from it and finally, from graphic designers’ external social worlds. This research suggests that contextual knowledge also needs to be brought into the teaching of graphic design, rather than being seen to arise implicitly in conceptualisation and studio practice.